Romantic genius and the literary magazine : biography, celebrity and politics - Higgins, David Minden, 1974- (Routledge studies in romanticism, 2005)
Considering how literary magazines in early nineteenth-century Britain debated the nature of genius, as well as how and why they constructed particular creative artists as geniuses, this is an important work for anyone working on Romantic literature.